Poliittinen karikatyyri suomalaisissa pilalehdissä 1868-1917 : taidehistoriallinen ja -teoreettinen tutkimus poliittisen karikatyyrin olemuksesta ja viestintäkeinoista - Mylläri, Juhani (1983)
The study examines political caricatures published in satirical magazines in Finland between 1868 and 1917. Between these years, at least 344 satirical magazines were published under different names, of which 11 titles were examined in this study. The criteria for selection were that they contained caricatures with a political standpoint, drawn by Finnish caricaturists who had carried out such work for several years, and that the satirical magazines were regularly published for a long time. Foreign models, printing techniques and political circumstances influenced the political caricatures published in satirical magazines and their development. Based on the factors above, the Finnish political caricature can be divided into three phases, which last from 1868-1894, from 1895-1902, and from 1903-1917. The most important topics covered were the question of the relationship of a dependent Finland with Russia, the language question between the Finnish and Swedish speakers, the position of the working class, the parliamentary reform of 1906, and the events in the year of revolution, 1917. All the major parties published a satirical magazine supporting their own aims. The research concerns art history. For this reason special attention has been paid to insights concerning the content of the caricatures and the formal structure which conveys it. The artist chose the composition, the style of the caricature, the degree of caricature, and the humorous tone according to what was to be said or the nature of the event. All the features of the caricature were planned on the basis of how the picture was transmitted and what effect it was meant to have. This was also the case when, in order to simplify and clarify the topic, the idea of the picture was presented with the help of myth, allegory or symbol, or if emblems or attributes were given to them. Caricature variants of well-known patriotic works of art were also popular because of the emotional effect of the models on which they were based. It is no longer easy to discover how the message of the political caricatures was received, except through oral recollections or arbitrarily written chronicles. The clearest picture of their political effects can perhaps be recovered by an examination of the cencorship procedures: legal injunctions were constantly taken out, one magazine was suppressed, and three people were imprisoned.